Interfacial Bonding Mechanism and Mechanical Performance of Continuous Fiber Reinforced Composites in Additive Manufacturing - Fan, Congze; Shan, Zhongde; Zou, Guisheng; Zhan, Li; Yan, Dongdong (Chinese journal of mechanical engineering, 2021)
The additive manufacturing of continuous fiber composites has the advantage of a high-precision and efficient forming process, which can realize the lightweight and integrated manufacturing of complex structures. However, many void defects exist between layers in the printing process of additive manufacturing; consequently, the bonding performance between layers is poor. The bonding neck is considered a key parameter for representing the quality of interfacial bonding. In this study, the formation mechanism of the bonding neck was comprehensively analyzed. First, the influence of the nozzle and basement temperatures on the printing performance and bonding neck size was measured. Second, CT scanning was used to realize the quantitative characterization of bonding neck parameters, and the reason behind the deviation of actual measurements from theoretical calculations was analyzed. When the nozzle temperature increased from 180 to 220 °C, CT measurement showed that the bonding neck diameter increased from 0.29 to 0.34 mm, and the cross-sectional porosity reduced from 5.48% to 3.22%. Finally, the fracture mechanism was studied, and the influence of the interfacial bonding quality on the destruction process of the materials was determined. In conclusion, this study can assist in optimizing the process parameters, which improves the precision of the printing parts and performance between the layers.